Karshin volost and Karshin people in Bashkiria in the 18th century - Urakov, Dilshodbek Z.; Shonazarov, Shuxrat B. (Journal of the Belarusian State University. History, 2025)
The history of the Karshin volost (one of the volosts of Bashkiria in the 18th century) and the question of the integration of the Karshin people into the population of Bashkiria are studied. Their native settlement, named after clan, was called «Karshin». It is likely that the ethnonym «Karshin» is derived from the word «Karshi» and denotes a palace or fortress guard. In the second third of the 18th century, there was migration of settlers from Central Asia to the south-eastern borders of Russia. The term «Karshilik» was mainly used by the population of Eastern Bukhara to refer people originating from Karshi or the Karshin oasis. The first area of settlement of the tribe was the left bank of the Belaya River. The patrimony of the Bashkirs of the Karshin clan encompassed the entire valley of the Karmasan River. After the annexation of Bashkiria to the Russian state, the latter’s government secured the lands occupied by Bashkir communities based on estate law. It is believed that the Bashkirs were the first to take up agriculture. They were patrimonial landowner, whereas other peoples were settlers who did not have their own allotments and lived on Bashkir lands. The inhabitants of the Karshin volost linked the history of their settlement with the name of Sharip Mryakov. Archival documents have been preserved testifying to the service of Bashkir Karshin people in the Kasimov Khanate. It is noted that the Bashkirs were loyal to the Russian administration.
Keywords: ethnos; foreigners; Karshin volost; Karshin; migration; palace; guard; Bashkirs; Russia; Central Asia; patrimony; agriculture; settlements; administration; foreman; service